Finite Element Simulation of Repeated Upsetting at Elevated Temperature. Issue 1 (March 2020) - Guo, Wei; Zou, Jin; Liu, Keming
Abstract: The equivalent strain field, effective stress field, and temperature field of the billet after repeated upsetting were analyzed by using finite element simulation software. The results show that the average equivalent strain in the billet improves with the increase of processing pass. At the same pass, the strain in the middle of upper surface is the smallest and in the middle of lower surface is the largest. After three passes, maximum strain of 5.33 is achieved. The equivalent stress and temperature decrease gradually from the middle to both sides of the billet.